Bianchi type I vacuum, field in Brans-Dicke theory - Ram S.; Singh D.K. (My University, 2025)
An exact solution of the vacuum Brans-Dicke field equations is obtained for the metric tensor of a spatially-homogeneous and anisotropic Bianchi type I configuration. The solution has no analogy in Einstein's theory for the layer values of the BD parameter. Some properties of the solution are discussed. © 1983 D. Reidel Publishing Co.